Classroom assessment methods used by level one ESL primary school teachers: A case study in Samarahan District / Diana Menau Jantan - Jantan, Diana Menau (2016)
Assessment plays a major role in an education system. In order to equip our srudents in this competitive global environment, School Based Assessment was implemented to improve education system in Malaysia which had been centralised and summative 'in nature.. This study investigated the assessment methods used by Level One ESL teachers in Samarahan District and explored the reasons for using those assessment methods. This mixed-method study utilized multistage random sampling Data was collected using Assessment Preference Inventory by Zhang & Burry-Stock (2003) from 103 respondents and 44 respondents were interviewed . Findings showed that Level One ESL teachers used all assessment methods in their classrooms namely Perfonnance Assessment, Standardized Testing, Paper-pencil Test. Communicating Assessment Results and on-achievement Based Grading. Besides. the findings showed that teachers used different types of assessment methods in their classrooms because of many reasons such as policy, class size and feedback. The findings had contributed information on bow school based assessment was conducted in ESL classrooms in Samarahan district.